Gramàtica històrica catalana: proposta d’un mètode d’estudi - Casanova, Emili (Caplletra. Revista Internacional de Filologia, 2015)
This article provides a practical, productive and comprehensive method to study the various materials (diachronic and synchronic) related to Catalan historical linguistics. It follows the models described by Malkiel, Varvaro, and Granda.